Simile in Harry Potter and The Chamber of Secrets - Sri Rahmadhani Siregar; Widyanra Pane (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2020)
This research focused on simile analysis and meaning on Harry Potter and The Chamber of Secrets novel. Simile is a figurative language that makes a comparison, showing similarities between two different things. Qualitative research is used in conducting this research. The result of the research has found 55 sentences of Simile on Harry Potter and The Chamber of Secrets from chapter one up to chapter nine. The author used Simile to describe emotion of characters, to explain circumstances and to raise the interesting impression in the novel.